Efficacy and Safety of Long-Term Dual Antiplatelet Therapy: A Systematic Review and Meta-Analysis - Xiaoming Zhang MD; Da Zhou PhD; Siying Song PhD; Xiangqian Huang MD; Yuchuan Ding PhD; Ran Meng MD, PhD (Clinical and Applied Thrombosis/Hemostasis, 2024)
Background Dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 inhibitor is a standard therapy in patients with ischemic vascular diseases (IVD) including coronary artery, cerebrovascular and peripheral arterial diseases, although the optimal duration of this treatment is still debated. Previous meta-analyses reported conflicting results about the effects of long-term and short-term as well as non-DAPT use in various clinical settings. Herein, we conducted a comprehensive meta-analysis to assess the efficacy and safety of different durations of DAPT. Methods We reviewed relevant articles and references from database, which were published prior to April 2023. Data from prospective studies were processed using RevMan5.0 software, provided by Cochrane Collaboration and transformed using relevant formulas. The inclusion criteria involved randomization to long-term versus short-term or no DAPT; the endpoints included at least one of total or cardiovascular (CV) mortalities, IVD recurrence, and bleeding. Results A total of 34 randomized studies involving 141 455 patients were finally included. In comparison with no or short-term DAPT, long-term DAPT reduced MI and stroke, but did not reduce the total and CV mortalities. Meanwhile, bleeding events were increased, even though intracranial and fatal bleedings were not affected. Besides, the reduction of MI and stroke recurrence showed no statistical significance between long-term and short-term DAPT groups. Conclusion Long-term DAPT may not reduce the mortality of IVD besides increasing bleeding events, although reduced the incidences of MI and stroke early recurrence to a certain extent and did not increase the risk of fatal intracranial bleeding.